2016
DOI: 10.1371/journal.pone.0164306
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Antimicrobial Resistance Patterns of Urinary Escherichia coli at an Australian Tertiary Hospital: Time Series Analyses of Prevalence Data

Abstract: This study describes the antimicrobial resistance temporal trends and seasonal variation of Escherichia coli (E. coli) urinary tract infections (UTIs) over five years, from 2009 to 2013, and compares prevalence of resistance in hospital- and community-acquired E. coli UTI. A cross sectional study of E. coli UTIs from patients attending a tertiary referral hospital in Canberra, Australia was undertaken. Time series analysis was performed to illustrate resistance trends. Only the first positive E. coli UTI per p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 40 publications
4
34
1
7
Order By: Relevance
“…However, at continental level, higher rates of resistance were informed, as was the case of low-UTI strains (70%) in Uruguay. In Australia, the main resistance prevalence to trimethoprim from 2009 to 2013 was still lower (20.6%) than what was reported in this research [13,16,18,26].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, at continental level, higher rates of resistance were informed, as was the case of low-UTI strains (70%) in Uruguay. In Australia, the main resistance prevalence to trimethoprim from 2009 to 2013 was still lower (20.6%) than what was reported in this research [13,16,18,26].…”
Section: Discussioncontrasting
confidence: 68%
“…Previously, a higher frequency of gentamicin resistance (22.6%) was reported for E. coli in elderly Argentinian patients and in Enterobacteriaceae from Italian elderly (over 30%). In contrast, a significantly lower average prevalence (3.7%) of gentamicin resistance was detected during a 5-year period for community urinary E. coli isolates from Australia [13,19,26].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the temporal changes of resistant pathogens responsible for documented HAIs is crucial in understanding the local epidemiology of HAI and improving local antimicrobial and infection control practices [9]. These trends are probably reflecting several interplaying practices/factors such as antimicrobial consumption [10,11], infection control practices [12], environmental cleaning [13], and community burden [14].…”
Section: Introductionmentioning
confidence: 99%
“…CFC/ml on urine culture (15). However, Fasugba et al (16) was the only exception since it included samples only when more than 10 7 CFC/ml. sparse infection (<10 5 CFC/ml in association with UTI symptoms) and that did not specify the UTI subtype.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rodrigues et al , 2016 reported resistance in CA-UTI annually and consecutively from 2010 to 2015 (13); accordingly, their study was considered as six papers. Similarly, Fasugba et al, 2016 detected the resistance in both CA and HA cases over five years; they reported ten cohorts(16) Alqasim et al, 2018. (two cohorts) compared the ciprofloxacin resistance in two E. coli strains(23).…”
mentioning
confidence: 99%